ROLE OF COLORS IN PAINTINGS OF DISABLED PAINTERS: विकलांग चित्रकारों के चित्रों में रंगों की भूमिका - Sharma, Poonam (International Journal of Research -GRANTHAALAYAH, 2014)
Life is incomplete without colors. Colors have special importance in the paintings of disabled painters. Forced to live a dull life, these artists, even after physical disabilities, adopt specific combinations of colors in their paintings, giving them life, giving them life, the silent expression of the pictures is so strong. Even the dreamer cannot think that the person making this painting is handicapped. The selection of colors of such special artists is very unique. Due to the different colors of the characters, we are able to find the name of the particular character. Special attention is placed on the value of colors in the paintings of these artists, the use of aura and shadow is visible through the medium of light and darkness. रंगों के बिना जीवन अपूर्ण है। विकलांग चित्रकारों के चित्रों में रंगों का विशेष महत्व है नीरस जीवन जीने को मजबूर ये कलाकार शारीरिक अक्षमताओं के उपरांत भी अपनें चित्रों में रंगों के विशिष्ट संयोजन कर, उन्हें जीवित रुप प्रदान कर , प्राण डाल देते हैं ,चित्रों द्वारा मूक अभिव्यक्ति इतनी सशक्त होती है कि देखने वाला स्वप्न में भी यह नहीं सोच पाता कि इस चित्र को बनाने वाला विकलांग है। ऐसे विशेष कलाकारों के रंगों का चयन अति विलक्षण होता है। वर्णों की विभिन्न रंगतों के कारण ही हम वर्ण विशेष का नाम ज्ञात कर पाते हैं। इन कलाकारों के चित्रों में रंगों के मान का विशेष घ्यान रखा गया है, प्रकाश व अंधकार के माघ्यम से आभा एवं छाया का प्रयोग दर्शनीय है चित्रों में सधनता युति-द्युति का अनुपम प्रयोग किया गया है।